2012
DOI: 10.1007/s10456-012-9270-4
|View full text |Cite
|
Sign up to set email alerts
|

Usnic acid inhibits breast tumor angiogenesis and growth by suppressing VEGFR2-mediated AKT and ERK1/2 signaling pathways

Abstract: Tumor growth depends on angiogenesis and inducing angiogenesis is one of the most important hallmarks in the cancer development. Treatment with small molecules that inhibit angiogenesis has been an effective strategy for anti-cancer therapy. Some anti-angiogenic factors are derived from traditional Chinese herbs. Usnic acid (UA), an active compound mainly found in lichens, has shown some biological and physiological activities. However, the role and mechanism of UA in tumor angiogenesis are still unknown. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 49 publications
5
99
0
Order By: Relevance
“…The wound-healing migration assay was performed as described previously (22). Briefly, HUVECs were treated with mitomycin-C to inactivate cell proliferation, wounded by a microtip, washed with PBS, supplemented with fresh medium with or without VEGF (20 ng/mL) and treated with SAD.…”
Section: Wound-healing Migration Assaymentioning
confidence: 99%
“…The wound-healing migration assay was performed as described previously (22). Briefly, HUVECs were treated with mitomycin-C to inactivate cell proliferation, wounded by a microtip, washed with PBS, supplemented with fresh medium with or without VEGF (20 ng/mL) and treated with SAD.…”
Section: Wound-healing Migration Assaymentioning
confidence: 99%
“…VEGFR2-mediated activation of Akt, ERK, JNK, and p38 MAP kinase contributes to VEGF-induced survival, proliferation, migration, and tubular-network formation of endothelial cells (Zachary and Gliki, 2001;Wu et al, 2006;Dellinger and Brekken, 2011;Song et al, 2012). Our data showed that L-carbocisteine significantly abrogated ERK activation specifically in endothelial cells; no effect was observed in epidermal cells (Figs.…”
Section: L-carbocisteine Is a Novel Inhibitor Of Tumor Angiogenesismentioning
confidence: 60%
“…To evaluate the molecular mechanisms associated with L-carbocisteine-induced inhibition of VEGF-dependent angiogenesis, we measured by Western blotting the phosphorylation of key proteins downstream of VEGFR2 activation: Akt, ERK1/2, JNK, and p38 MAP kinase (Wu et al, 2006;Dellinger and Brekken, 2011;Song et al, 2012;). L-Carbocisteine (100 mM) potently suppressed VEGF-induced ERK1/2 activation in HUVECs but had no effect on activation of Akt, JNK, or p38 MAP kinase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Zu et al and our study provide similar results of alternative source-induced apoptosis of cancer cells. Song et al found that treatment with usnic acid significantly suppresses mouse corneal neovascularization via inhibiting vascular endothelial growth factor (VEGF)-activated VEGFR2 phosphorylation (Song et al, 2012). It was determined that usnic acid functions as a tumor angiogenesis inhibitor by suppressing VEGFR2-mediated AKT and extracellular signal-regulated kinase (ERK 1/2) signaling pathways.…”
Section: Discussionmentioning
confidence: 99%